Attitudes toward violence against women and the factors that affect them in kutahya, turkey - (:unkn) unknown (Women's Health and Action Research Centre, 2019)
This cross-sectional descriptive study was conducted to determine the attitudes of women and men living in Kutahya, Turkey towards violence against women, and the factors that affect them. The data were collected using an Information Form for Women, an Information Form for Men, and the Attitude towards Violence Scale. The study was completed with 2959 participants; 1481 women and 1478 men. In the study, 41.3% of the women and 22.6% of the men reported being subject to violence. The mean score of the attitude towards violence scale was 41.57±11.83 for women and 49.38±11.52 for men (p<0.001). The mean scores on the attitude towards violence scale were found to be statistically significantly related to gender, educat ion status, occupation, income status, co-educational status, co-occupation, marital age, family type, and subjection to violence (p<0.05). Socio-demographic and socio-cultural factors were found to influence the attitudes of women and men towards violence against women. The attitudes towards violence against women were found to be more positive in women. The rate of accepting violence as natural (acceptable) phenomena was found to be higher among men. That is, the attitudes of men towards violence against women are closer to the traditional approach, away from the modern approach. © 2019, Women's Health and Action Research Centre. All rights reserved.
Keywords: Attitude; Factors affecting violence; Turkey; Violence against women